Alat Akuisisi Data 5 Parameter Sinyal Fisiologis Sebagai Penciri Stress Pada Manusia Berbasis Arduino MEGA - Putri Madona; Suci Wulandari (Politeknik Caltex Riau, 2022)
Stress is a non-specific response of the body to any demands on the body. It refers to events that are felt to be harmful to a person's physical and psychological well-being. One of the effects of stress on humans is depression. Depression that is allowed to continue can cause a decrease in work productivity, impaired social relationships to suicidal ideation. Increased stress due to lifestyle and current conditions has prompted many studies to be able to perform early detection of stress by measuring physiological signals. This study makes a tool to acquire data from 5 physiological signals of the body to later be used as variables for analyzing stress levels in humans. This tool uses an MPX5050DP sensor for blood pressure, a pulse sensor for heart rate detection, a DS18b20 sensor for body temperature, a sound sensor to calculate respiration frequency and a GSR sensor to measure the resistance value of human skin. The sensor will take data from the measured physiological parameters which will then be displayed on the LCD screen. The test was carried out on 5 test subjects with each subject taking data 5 times. The error rate of each parameter is obtained as follows: heart rate sensor 1.14%, temperature sensor 0.36%, blood pressure sensor 11.2% for systolic measurement and 4.9% for diastolic measurement, and respiration sensor 22.08 %.